1991
DOI: 10.1002/bjs.1800780309
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal complications in 4473 patients who underwent cardiopulmonary bypass surgery

Abstract: Thirty-nine gastrointestinal complications occurred in 35 of 4473 patients (0.78 per cent) who underwent surgery involving cardiopulmonary bypass during an 8-year period. The mortality rate when one of these complications occurred was 22 (63 per cent) representing 11.5 per cent of the 191 deaths from all causes in the series. The relative risk of developing a gastrointestinal complication was 1:249 when the heart was not opened, 1:66 when it was and 1:5 after cardiac transplantation. Gastrointestinal bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 14 publications
5
62
0
Order By: Relevance
“…Concomitant CABG in addition to mitral valve surgery was also reported to be predictive of GI complications by multivariate analysis by Mohavedi and his coauthors, 14) who explained this correlation by longer bypass time The relationship between chronic renal failure (CRF), acute renal failure (ARF) and GI complications after cardiac surgery has been studied in several univariate 20,21) and multivariate 3,14) analysis publications. In our experience CRF is an independent determinant for GI complications.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant CABG in addition to mitral valve surgery was also reported to be predictive of GI complications by multivariate analysis by Mohavedi and his coauthors, 14) who explained this correlation by longer bypass time The relationship between chronic renal failure (CRF), acute renal failure (ARF) and GI complications after cardiac surgery has been studied in several univariate 20,21) and multivariate 3,14) analysis publications. In our experience CRF is an independent determinant for GI complications.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports suggested that expeditious surgery was the key to succeed in treating NOMI. 13,14) In conclusion, if patients, especially those with a highrisk condition, who had undergone a major cardiovascular operation, suffer from vague, abdominal symptoms early, postoperatively; NOMI, an almost fatal complication unless expeditiously treated, should be considered as one of the presumed causes. Although nonspecific, confusion/ delirium, lactic acidosis, abnormal intestinal gas and distention on roentogenogram may help suspect its presence.…”
Section: )mentioning
confidence: 99%
“…7 Pancreatitis has also been reported after heart and heart-lung transplantation, particularly when cardiopulmonary bypass was used. 8 Acute pancreatitis after OLT is an uncommon complication. Of 1,832 adult patients who underwent 2,161 OLT procedures, Krokos et al 2 reported 247 patients (13.4%) who developed biochemical pancreatitis and 55 patients (3%) who developed clinical pancreatitis; 35 of these died (67.3%).…”
Section: Discussionmentioning
confidence: 99%